2006
DOI: 10.1177/0091270006291031
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Amlodipine Besylate/Atorvastatin Calcium Combination Tablet

Abstract: The bioequivalence of combination tablets containing amlodipine besylate/atorvastatin calcium with coadministered matching doses of amlodipine besylate and atorvastatin calcium tablets was investigated in randomized, 2-way crossover studies in healthy volunteers (N = 126). Subjects received a single dose of the amlodipine/atorvastatin tablet or coadministered matching doses of amlodipine and atorvastatin at the highest (10/80 mg; n = 62) and lowest (5/10 mg; n = 64) dose strengths. Atorvastatin geometric mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…In the Patel et al [22] study, patients taking single-pill amlodipine atorvastatin were almost twice as likely to be adherent compared with those taking a twopill amlodipine and atorvastatin regimen, and nearly three times more likely to be adherent than those taking other two-pill CCB and statin regimens at 6 months, with a greater benefit after 1 year of follow-up. Since there is no known difference in efficacy or tolerability between single-pill amlodipine atorvastatin and treatment with coadministered amlodipine and atorvastatin, [20,21,33,34] it is likely that these adherence benefits are related to other factors associated with single-pill therapy, such as a lower pill burden, [1,16,35] synchronization of therapy initiation, [1,19] or reduced co-payment costs, [17,18] all of which have been demonstrated to influence adherence in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the Patel et al [22] study, patients taking single-pill amlodipine atorvastatin were almost twice as likely to be adherent compared with those taking a twopill amlodipine and atorvastatin regimen, and nearly three times more likely to be adherent than those taking other two-pill CCB and statin regimens at 6 months, with a greater benefit after 1 year of follow-up. Since there is no known difference in efficacy or tolerability between single-pill amlodipine atorvastatin and treatment with coadministered amlodipine and atorvastatin, [20,21,33,34] it is likely that these adherence benefits are related to other factors associated with single-pill therapy, such as a lower pill burden, [1,16,35] synchronization of therapy initiation, [1,19] or reduced co-payment costs, [17,18] all of which have been demonstrated to influence adherence in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is a single-tablet FDC of the dihydropyridine calcium channel antagonist amlodipine, targeting high blood pressure, and the HMG-CoA reductase inhibitor atorvastatin, targeting hypercholesterolemia. The bioavailability of amlodipine and atorvastatin with the FDC was not significantly different from that with coadministered separate amlodipine and atorvastatin tablets [38]. Amlodipine/atorvastatin offers a convenient and effective approach to improving adherence and managing CV risk in hypertensive patients with dyslipidemia or at risk of CVD [30].…”
Section: Atorvastatin Plus Sitagliptinmentioning
confidence: 99%
“…Two studies examining the pharmacokinetic properties of co-administered amlodipine and atorvastatin have been published. The first of these studies demonstrated that amlodipine does not affect the pharmacokinetic properties of atorvastatin, and vice versa, under fasting conditions 39. The second of these studies demonstrated that the bioavailability of both agents is unchanged when they are administered with food 40.…”
Section: Rationale For the Combination Of Amlodipine And Atorvastatinmentioning
confidence: 99%